FISH CATCHING COMPOSITION OF FISHING GEAR PAYANG AT TIME MORNING AND AFTERNOO IN THE WATERS PASALABAN SOUTHERN BUNGUS PADANG WEST SUMATERA - Muhammad Zikrillah; Pareng Rengi; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Payang is seine net used for catching schooling fish (pelagic fish) on the surface of the water. Both wings are useful for scaring or surprising and herding fish into bags. The method of  operation is to encircle the fish hordes and then the bag is pulled to the boat. The purpose of this study was to determine the composition of the catch of the fishing gear payang in the morning and afternoon. This research was conducted on 25 february – 03 march 2019 in the waters Pasalaban Southern Bungus Padang West Sumatera. The method used in this study is a survey method with direct data collection. The type of cacth is payang fishing gear is tuna fish (Euthynnus affinis), kapak fish (Mene maculata), skipjack tuna (Katsuwonus pelamis), barred mackerel fish (Scomberomorini comersinii), anchovy (Stelephorus sp), pompano fish (Caranx ignobilis), and long jawed mackerel (Rastrelliger sp). Total catch weight in the morning is 75,63 kg and catch wieght in the afternoon is 132,34 kg. The number of individuals caught in the morning is 1.194 tails and in the afternoon is 1.092 tails. The number of individuals in the morning is more than the amount of the time in the afternoon and for the total weight of the catch in the afternoon more obtained from the morning.Key Word:Payang, composition of fishing gear, Bungus, Padang, West Sumatera